Notch signaling in the pancreas: patterning and cell fate specification. (6th December 2012) - Afelik, Solomon; Jensen, Jan
Abstract: Notch signaling is an evolutionarily conserved mechanism adapted to control binary fate decisions. The first evidence of Notch in pancreatic development focused on its critical role in controlling endocrine fate decisions. Since then, we have come to understand that this signaling system operates iteratively in the pancreas, and is not limited to the control of endocrine fate decision. Notch appears to play a role in early organ development, then during organ domain patterning, and only during a final refinement process, in the control of terminal cell fates. In so doing, Notch receptors and their ligands are under the influence of a wealth of genetic components that together help orchestrate the building of a complex, glandular organ. WIREs Dev Biol 2012, 2:531–544. doi: 10.1002/wdev.99 This article is categorized under: Establishment of Spatial and Temporal Patterns > Repeating Patterns and Lateral Inhibition